A new triterpene saponin from Fagonia schimperi - Howayda Ismail, Mohamed E. Mostafa, Amr El-Demerdash,, Dalia M. Hanna, Mamdouh Abdel-Mogib (Journal of Applied Pharmaceutical Science, 2020)
Chemical investigation of the whole Fagonia schimperi C. Presl plant yielded a new triterpene saponin, namely 3-O-β- xylopyranosyl-(1→2)-α-L-arabinopyranosyl-27-hydroxyoleanolic acid 28-O-β-glucopyranoside (1), along with five known natural products 2–6. Structures of the isolated compounds were elucidated by intensive spectroscopic methods including Electrospray Ionisation-Mass Spectrometry (ESI-MS) and 1D and 2D-NMR, which matched the literature data. Fagonia schimperi crude saponin fraction, ethyl acetate (EtOAc) fraction, and the new compound (1) were investigated for their biological activities as antibacterial, antioxidant, and cytotoxicity. EtOAc fraction and compound (1) were the most potent agents, wherein they displayed potent antibacterial activity against both Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa). Additionally, the EtOAc fraction displayed potent antiproliferative activity against hepatocellular carcinoma and mammary gland with IC50 values of 7.38 ± 0.4 and 4.89 ± 0.3 μg/ml, respectively. Furthermore, compound 1 showed a significant cytotoxic activity against the two cell lines with IC50 values of 19.20 ± 1.4 and 8.18 ± 0.9, μg/ml, respectively. This comes in agreement with the antioxidant activity that was assessed by 2,2,1-diphenyl-1-picrylhydrazyl and SOD-like activity methods in the following order: EtOAc fraction > compound 1 > crude saponin fraction.
Keywords: Fagonia schimperi, triterpene saponins fraction, antibacterial, antioxidant, cytotoxicity.